A Study of the Epistemological Principles of Ghazālī and Mullā Sadrā and Their Implications to Rational Training - Mohammad Alaei; Saeed Beheshti; Ahmad Salhshouri (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present research is to study the epistemological principles based on the viewpoints of Abū Hāmid Muhammad Ghazālī and Mullā Sadrā and to infer their arguments in the field of rational training with emphasis on the pedagogical objectives and methods. The type of research is qualitative and its method is analytical, comparative, and inferential. The findings showed that the two thinkers have commonalities in some epistemological principles and differences in some other cases. The objectives of rational training based on their commonalities include: reason as a potential for acquiring knowledge by everyone, reason as the source of cognition, nature (the world’s creatures) as the source of cognition, heart as the source of cognition, reinforcement of the outer senses (eyesight, hearing, smelling, taste, and touch), reinforcement of the inner senses (imagination), observation of the hierarchy (from simple to complex and abstract) in education and presentation of theology and science, tendency to metaconceptual (true) cognition as an objective for classroom teaching, … . Moreover, the differences involve the following subjects: obtaining the essence of objects and the substantiation of imagery in minds, priority of the sensual to rational knowledge, acquaintance with the history and biography of the ancestors, boosting insight, rational perfection by the aid of theology and religious instruction, unity between the knower and known, seeking assistance from the holy religion (the Qur’an, Ahādith, and tradition), acknowledgment of the religious sources as a criterion to assess education, attempts in line with self-awareness in the process of education, … .